AB0010 Association of Gene Polymorphisms in ETS-1 with Rankl in Rheumatoid Arthritis. (15th July 2016) - Chen, L.; Huang, Z.; Yang, B.; Cai, B.; Su, Z.; Wang, L.
Abstract : Background: Rheumatoid arthritis (RA) is a complicated autoimmune disease characterized by progressive destruction of cartilage and bone. Recently, receptor activator of nuclear factor κB ligand (RANKL) have been found to be involved in the differentiation of osteoclasts [1]. Also, the association between the RANKL expression and the pathogenesis of bone-destructive rheumatoid arthritis (RA) has been described in several joints [2]. It indicated that RANKL play a crucial rule in RA. Meanwhile, E26 transformation specific sequence 1 (ETS-1), belonging to the ETS family of transcription factors that regulate the expression of various immune-related genes, was reported to confer susceptibility and development to RA [3]. Moreover, ETS-1 was found to be overexpressed in RA synovial membrane and to be involved in the destructive pathway of RA [4], but it was not clearly defined. Objectives: We aimed to identify how RANKL changes in RA and whether polymorphisms in ETS-1 play a role in that changes by describing in Chinese Han population. Methods: 170 RA patients and 136 healthy controls were included for this analysis. Clinical information was gathered and disease activity was determined according to the disease activity score for 28 painful/swollen joints (DAS28). The serum level of RANKL were detected by magnetic luminex assays. Four single nucleotide polymorphisms (SNPs) in ETS-1 were genotyped by high resolution melting (HRM) curve method. Results: Compared with healthy controls, Level of RANKL in serum of patients was elevated (28.69 (17.24–44.90) versus 14.24 (17.00–20.00), P<0.01). The RA patients with rs73013527 TT genotype had higher RANKL levels (P=0.019 in a dominant model). Furthermore, we found that T allele of rs73013527 was overrepresented in RA group as well (25.7% versus 42.6%, P<0.001). Besides, an association was found between rs73013527 TT genotype and DAS28 (P=0.001). No statistically significant difference was observed in the distribution of other three SNPs (rs10893872, rs4937333 and rs11221332) alleles or genotypes in this study (all P>0.05). Conclusions: This study suggests that RANKL increased in RA and the polymorphisms in the ETS-1 region may be associated with the changes of RANKL in RA. The patients with rs73013527 TT genotype may be not prone to RA but have higher RANKL which could lead a sever condiction. However, larger studies, most likely through multicenter collaboration will be needed to fully validate the significance of these findings. References: Motiur Rahman M, Takeshita S, Matsuoka K, et al. Proliferation-coupledosteoclast differentiation by RANKL: Cell density as a determinant of osteoclast formation [J]. Bone, 2015, 81:392–399. Liu WW, Xu ZM, Li ZQ, et al. RANKL, OPG and CTR mRNA expression in the temporomandibular joint in rheumatoid arthritis. Exp Ther Med. 2015 Sep;10(3):895–900. Chen L, Huang Z, Yang B, et al. Association of E26 Transformation Specific Sequence 1 Variants with Rheumatoid Arthritis in Chinese Han Population. PLoS One. 2015 Aug 4;10(8):e0134875. Redlich K, Kiener HP, Schett G, Tohidast-Akrad M, Selzer E, Radda I, et al. Overexpression of transcription factor Ets-1 in rheumatoid arthritis synovial membrane: regulation of expression and activation by interleukin-1 and tumor necrosis factor alpha. Arthritis Rheum. 2001;44:266–274. Disclosure of Interest: None declared